Comparing Security Practices of Workplace And Home: A Case For USIM Staff - Hamida Omar Issa Asker
The development of Information and Communication Technologies (ICTs) is becoming, very common throughout society. Therefore. it is a must to protect information asset. In addition to the technological aspect. research Continues to confirm the need to enhance security awareness among, employees. The objective of this study is to investigate the factors that may impact users' practice and awareness both in workplace and home. Specifically, factors such as policy, behaviour, training knowledge of IT and education were tested. In addition, the second objective of this study is to investigate the information security awareness and practice level among the employees. To achieve the study objectives, a quantitative methodology was applied: specifically a survey instrument was developed to measure if each of the key factors has a Significant association within the security awareness and practice both in workplace and home. 285 usable surveys were Collected from USIM employees and analyzed using Bivariate/Pearson Correlation and Linear Regression to determine the relationship between the independent variable and the dependent variable. The findings of the study revealed that there was a positive correlation between policy. behaviour, training, knowledge of IT and education with scanty awareness and practice both in workplace and honk. However, Linear Regression tests yielded no significant relationship between training factor and security awareness and practice both in workplace and home. These results indicated that security awareness and practice le\cl of employees, both in workplace and home are at high level. It is hoped that the present Study provides initial step to focus on security training Sessions among L'51ł employees to reflect new know ledge on the importance of security training to increase the knowledge of information security.